Antineutrophil cytoplasmic antibody-associated vasculitis in a patient with diffuse scleroderma - B N Shiva Prasad; H A Karthik Urala (Indian Journal of Rheumatology)
Scleroderma is a multiorgan connective tissue disease characterized by autoantibody production and fibroproliferative stenosis of the microvasculature. The development of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis in patients with scleroderma is a rare association. Renal and pulmonary complications occur more frequently than expected in scleroderma/ANCA-associated vasculitis overlap. The definitive diagnosis usually made based on autoantibody titers and biopsy of involved tissue. We present a case of diffuse scleroderma with ANCA-associated vasculitis presenting with neurological symptoms.